Aralia wangshanensis (Araliaceae)—the legitimate name for Aralia franchetii - Deng, Yunfei (Phytotaxa, 2019)
Aralia Linnaeus (1753: 273) consists of approximately 65 species distributed in eastern to southeastern Asia and the Americas (Wen, 1993). In the past there has been much disagreement over whether Aralia should be recognized in a broad or narrow sense (Li 1942, Hoo & Tseng 1965, 1978, Shang 1985a, 1985b, Shang & Li 1990, Wen 1993, 2002, 2011, Wen et al. 2002, Xiang & Lowry 2007). The broad sense of Aralia is supported by recent studies on the basis of morphological characters and molecular evidence (Wen 1993, Wen et al. 2001, 2002), and therefore some segregated genera, Coudenbergia Marchal (1879: 514), Pentapanax Seemmann (1864: 290, 294), Hunaniopanax Qi et Cao (1988: 47), Neoacanthophora Bennet (1979: 283), Sciadodendron Grisebach (1858: 7), Parapentapax Hutchinson (1967: 56) and Megalopanax E. Ekman ex Harms (1924:122), are reduced to the synonymies of Aralia (Wen 1993. Wen et al. 2002). Wen (2011) divided the genus into six sections: sect. Aralia, sect. Dimorphanthus (Miquel 1840: 95) Miquel (1863: 6), sect. Humiles Harms (1896: 13), sect. Nanae Harms (1896: 12), sect. Pentapanax (Semm.) Wen (2002: 31) and sect. Sciadodendron (Griseb.) Wen (2011: 29).